The Effect of Digital Transformational Leadership, Learning Organization, Supportive Work Environment, and Organizational Commitment on Turnover Intention of Gen Z IT Employees at PT. XYZ - Puty Sherlyta; Ardi Ardi; Margaretha Pink Berlianto; Richard Andre Sunarjo (Publikasi Indonesia, 2025)
This study aims to analyze the influence of Digital Transformational Leadership (DTL), Learning Organization (LO), Supportive Work Environment (SWE), and Organizational Commitment (OC) on Turnover Intention (IT) at PT XYZ. Respondents in this study were employees from Generation Z, worked in the IT division, and had a minimum of one year of service. Data were collected through a questionnaire using the judgemental sampling method, with a sample of 172 respondents out of a minimum calculation of 142 based on the Krejcie & Morgan formula. The collected data was analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS). The results of the study show that Digital Transformational Leadership has a significant negative influence on Turnover Intention, as well as a significant positive influence on Learning Organization and Organizational Commitment. Learning Organization also has a significant negative effect on Turnover Intention and a significant positive effect on Organizational Commitment. Meanwhile, Supportive Work Environment (SWE) has a significant negative effect on Turnover Intention and a significant positive effect on Organizational Commitment. These findings affirm the importance of Digital Transformational leadership, a learning culture, and a supportive work environment in increasing organizational commitment and reducing the desire to change jobs in young employees in the technology field.